Immediate postoperative care on high dependency unit or ward following microvascular free tissue transfer: lessons learnt from a change in practice imposed during the COVID-19 pandemic. Issue 3 (April 2022) - James, P.; Bekiroglu, F.; Broderick, D.; Khattak, O.; Lowe, D.; Schache, A.; Shaw, R.J.; Rogers, S.N.
Abstract: The COVID-19 pandemic resulted in sudden changes to the established practice of using the high dependency unit (HDU) for the first night of postoperative care following microvascular free tissue transfer. Patients were managed instead on the head and neck ward. This retrospective case-note review aimed to report outcomes in consecutive patients treated before and during the pandemic, and to reflect on the implications of ward-based rather than HDU care. A total of 235 patients had free tissue transfer between 3 January 2019 and 25 February 2021: 125 before (lockdown 23 March 2020), and 110 during the pandemic (52 ward-managed and 58 HDU-managed). There were subtle case-mix differences during the pandemic, with 92% of ward-treated patients having oral cancers compared with 64% of HDU patients, and 73% of ward patients having a tracheostomy compared with 40% of HDU patients. Ward patients were less likely to receive electrolyte replacement (45% HDU vs 0% ward) and inotropes (12% HDU vs 2% ward). There were fewer returns to theatre for evacuation of a haematoma or re-anastomosis during the pandemic than there were before it. Other than fewer haematoma complications during the pandemic, the nature of complications was similar. In conclusion, the dramatic changes imposed by the pandemic have shown that the ward is a safe place for patients to be cared for immediately postoperatively, and it alleviates the bed pressures experienced in HDU. Careful case selection and clear criteria are required to identify patients who need the HDU.